Molecular characterization of Colletotrichum spp. associated with fruits in Brazil - Bragança, Carlos Augusto Dórea (2013)
Colletotrichum species are considered one of the most economically important plant pathogens. They cause many losses in tropical, subtropical and temperate regions affecting a wide range of plant species. In tropical and subtropical regions C. gloeosporioides and C. acutatum are associated with significant losses on pre and post-harvest anthracnoses. There are still many features to understand about Colletotrichum biology and its systematics. The accurate identification of species involved with each anthracnose is of high relevance to establish management strategies to control the disease. Although the great advances on Colletotrichum systematics, species complex such as C. gloeosporioides and C. acutatum are used in a broad sense in Brazil. These complexes were recently investigated and showed to be highly genetic and geographic variable. In this study multigene analysis were carried out based on ITS, GAPDH, CHS-1, TUB2 and CAL or HIS3 partial sequences for strains of C. gloesporioides and C. acutatum complexes collected from fruit crops in Brazil. Strains from different countries and exepitypes and others sequences available on GenBank from the species accepted on both complexes were added on dataset. Six strains from C. gloeosporiodes complex and five for C. acutatum were selected based on multigene phylogeny to investigate the pathogenicity through inoculations on detached fruit. The multigene phylogenies showed the occurrence of species in Brazil related to those complexes with a high genetic variability among them. The phylogeny of Brazilian strains belonging to the C. gloeosporioides complex showed that C. siamense represents the most genetically and host-specific variable clade. In contrast, C. asianum clade grouped only strains isolated from mango. The strains from this clade used on pathogenic test were not able to infect avocado and one of the strains caused symptoms only on mango. All strains from Brazil grouped in one subclade within the C. fructicola clade and seem to represent a genetically distinct group. C. theobromicola is first reported causing anthracnose on acerola fruit. Three new species (C. polyphialidicum, C. paranaense and C. pruni) belonging to the C. acutatum complex were recognized and their morphologic descriptions were provided. The pathogenic test for the strains in the C. acutatum complex showed their cross infection ability, but in some cases the larger lesions were produced on the original host. Most brazilian strains from C. acutatum complex grouped in one subclade within the C. nymphaeae clade and seem to be genetically distinct.